Micropropagation of Coffea sp. by somatic embryogenesis cultures technique - Hau, Nguyen Trung; Tuong Thu, Bui Thi; Minh, Tran Van (Academia Journal of Biology, 2012)
Coffee-leaves of in vitro plantlets and 2-year old plants were used as cultured materials. Callus was initiated on the medium MS + 2.4D (2 mg/l) + 2iP (2 mg/l) having rate of initiation 100% and 83%, induction 53% and 33% and growing 3.4 cm and 2.6 cm. Callus was proliferated on the medium MS + 2.4D (1 mg/l) + 2iP (4 mg/l) + adenine (60 mg/l) having growth rate index of yelloow soft-callus on leaves of in vitro and in vivo were 5.81 and 5.78. The growth rate was enhance when it’s supplemented more with 60 mg/l adenine giving rate index of 11.78 and 9.84. Somatic cell suspension were induced on the medium MS + malt (200 mg/l) + casein hydrolysate (100 mg/l) + 2.4D (1 mg/l) + 2iP (2 mg/l) + kinetin (1 mg/l) having early cultivation of cell mass 20 g/100ml in the volume of cell 3.847ml and growth rate index 1.05. The dynamic of cell suspension growth were determined in low growth in date of 0-7 days after culture, logarithm growth in 14-27 days and reach the highest growth in 28-35 days and declined afterward. Somatic cell suspension were proliferated on the medium MS + malt (200 mg/l) + casein hydrolysate (100 mg/l) + 2.4D (1 mg/l) + 2iP (2 mg/l) + kinetin (1 mg/l) supplemented with 30 g/l sucrose having the cell volume 3.847ml and growth rate index 1.05. Somatic cell suspension were differentiated to embryogenesis cell suspension on the medium MS + casein hydrolysate (400 mg/l) + adenine (40 mg/l) + BA (4 mg/l) + kinetin (1 mg/l) supplemented with somatic cell suspension at 4 subcultures, early mass cell cultivation at 20 g/100 ml, 30 g/l sucrose having cell density stimulation 0.9 ´ 104 cell/ml and stimulation index 75% transformed to embryogenesis cell. Embryogenesis cell suspension were plated and regenerated on the medium MS + malt (200 mg/l) + casein hydrolysate (100 mg/l) + BA (4 mg/l) + kinetin (1 mg/l) with cell suspension at 6 weeks of cultivation, the volume plated with 5 ml/60 ml having rate of regeneration of 97 shoots/5ml embryogenesis cell suspension. Shoots growth and development in vitro on the medium MS + BA (0.5 mg/l) having good growth after 8 weeks with 6 leaves/shoot, leaves size 4.8 cm2, shoot height 5.2 cm and it was favoured time to acclimatization nursery. Micropropagation of Coffea sp. via embryogenesis cultures technique was set up to produce 19,400 plants per liter of embryogenic embryo suspension.